Tinjauan Penerapan Klausula Baku Sepihak dalam Perjanjian Peer to peer lending - Wiliam; Dr. Nynda Fatmawati Octarina., S.H., M.H (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Peer-to-peer lending is a financial technology service in the field of unsecured cash loans that brings together lenders and borrowers through an internet-based electronic platform. Peer-to-peer lending greatly facilitates transactions for individuals without the need to queue or wait for loan disbursement decisions, unlike conventional banks that may appear complicated and have longer disbursement times. However, in practice, peer-to-peer lending providers often utilize standard clauses to expedite fund disbursement, which can potentially harm consumers. Standard clauses tend to place consumers in an imbalanced position, where peer-to-peer lending providers can unilaterally apply changes to the terms and conditions of the service without obtaining confirmation or consent from consumers. The aim of this research is to analyze whether the standard clauses used by peer-to-peer lending platform, violate the principle of the freedom of contract. This research adopts a normative legal research methodology, utilizing legislative and conceptual approaches in the analysis. The results of this study indicate that the application of standard clauses in the peer-to-peer lending platform agreement violates the principle of freedom of contract and puts consumers in an imbalanced position when closing a peer-to-peer lending agreement. Keywords: Standard clause; debt agreement; Peer to peer lending.